Emergence of dengue virus serotype 2 in Mauritania and molecular characterization of its circulation in West Africa. - Toscane Fourié (Public Library of Science (PLoS), 2021)
The number of sporadic and epidemic dengue fever cases have reportedly been increasing in recent years in some West African countries, such as Senegal and Mali. The first epidemic of laboratory-confirmed dengue occurred in Nouakchott, the capital city of Mauritania situated in the Saharan desert, in 2014. On-site diagnosis of dengue fever was established using a rapid diagnostic test for dengue. In parallel, the presence of Aedes aegypti mosquitoes in the city was confirmed. The initial diagnosis was confirmed by RT-PCR, which showed that all samples from the 2014 dengue epidemic in Nouakchott were dengue virus serotype 2 (DENV-2). The whole genome or envelope protein gene of these strains, together with other DENV-2 strains obtained from travelers returning from West African countries to France between 2016 and 2019 (including two Mauritanian strains in 2017 and 2018), were sequenced. Phylogenetic analysis suggested a recent emergence of an epidemic strain from the cosmopolitan genotype belonging to West African cosmopolitan lineage II, which is genetically distinct from African sylvatic genotype. The origin of this DENV-2 lineage is still unknown, but our data seem to suggest a recent and rapid dispersion of the epidemic strain throughout the region. More complete genome sequences of West African DENV-2 are required for a better understanding of the dynamics of its circulation. Arboviral surveillance and outbreak forecasting are urgently needed in West Africa.